Financial literacy among tin mining workers: A study of ethnography in East Belitung, Indonesia - Suranto, Suranto; Fitriani, Sofa Aji; Ardani, Amanda Putri; Susilo, Agus (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
The purpose of this research is to describe the level of financial literacy in East Belitung, to explore the challenges and constraints faced in the application of financial literacy, and to reveal the efforts to face challenges and constraints in the application of financial literacy. The research method used was ethnography with a qualitative approach. Data collection techniques of this study were interviews, observation, and documentation. In-depth interviews were conducted with village heads and the people of East Belitung. This study applied data reduction, data display, and verification as the data analysis steps. The results of this study indicated that the high income of people who work as tin miners triggered some people to have a consumptive lifestyle. The consumptive lifestyle is one aspect that shows that the level of financial literacy was still low and generated problems with family money management. The challenges and constraints in the application of financial literacy in East Belitung were consumptive lifestyles or habits that were inherent in the culture in society. Hence, it took time and effort to reduce these consumptive habits.